Urinary tract infection incidence in college students (Baghdad Science Journal, 2025)
Result of studying (61) urine samples collected from students department of Biology in the College of Education-Tikrit University and the people who hold signs and symptoms of urinary tract infections with those who do not have any signs or symptoms through a questionnaire has been with the collection of samples, and the total cases were infected (39 ) cases, a rate (63.9%) distributed (28) cases a female (68.2%) and male (11) cases event rate (55%), while the distribution of positive cases among age groups have emerged group (20-22 years) is the highest rate (56%) females. The results of urine cultures accompany the presence of different types of bacteria sick and E.coli bacteria is the highest ratios positive also it is the most common causative agents of urinary tract infections ,it is the predominant organism to be isolated. Less frequent causative Staphylococcus aureus . Susceptibility of isolates to various antimicrobial drugs was also studied. The result demonstrates the frequent incidence of resistant bacteria to commonly used drugs especially Ampicilline, Tetracyclin.